CORPUS-BASED MATERIALS: GRAMMAR TEACHING WITH CORPUS (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article is devoted to find out effectiveness of corpus-based materials in grammar teaching and students’ attitude towards corpus- based materials when they were used for first time in the language lessons. The experiment was taken  among the students in Uzbekistan whose native language is Uzbek .The participants were divided into two groups of experimental and control. Corpus –based materials were used with experimental group and control group were taught textbooks and course-books which were designed according to curriculum. The data were collected through tasks, questionnaires, interviews. And also control group students' answers and participation were observed and distinguished with experimental group. The statistical analysis showed that corpus-influenced grammar tasks effective than traditional grammar activities which based on given rule of grammar topic. Consequence of the experiment that the students wanted to use corpus sites to find common usage of grammar item in context.